2006
DOI: 10.1007/s00223-005-0201-x
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibromatosis Type 1 Gene Haploinsufficiency Reduces AP-1 Gene Expression without Abrogating the Anabolic Effect of Parathyroid Hormone

Abstract: Approximately 50% of neurofibromatosis type 1 (NF1) patients exhibit skeletal pathology, such as premature osteoporosis or pseudoarthroses. Loss of neurofibromin deregulates Ras signal transduction to affect generation of mitogen-activated protein kinase and Akt, both of which have been implicated in parathyroid hormone (PTH) anabolic mechanisms. Our aim was to determine if loss of neurofibromin impaired the anabolic effect of PTH on bone mass. Nf1 heterozygote (Nf1(+/-)) and wild type (Nf1(+/+)) mice were tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…While the mechanism of PTH action is different to BMP-2, we found that the PTH axis is retained in Nf1 þ/À calvarial osteoblasts, as has been recently reported. 34 Consistent with Nf1 being a negative regulator of the small GTPase Ras, Nf1 þ/À cells displayed increased Ras activity in a pull-down assay, although Ras activity was further increased by BMP-2 treatment (Fig. 1E).…”
Section: Tissue Histologymentioning
confidence: 56%
See 1 more Smart Citation
“…While the mechanism of PTH action is different to BMP-2, we found that the PTH axis is retained in Nf1 þ/À calvarial osteoblasts, as has been recently reported. 34 Consistent with Nf1 being a negative regulator of the small GTPase Ras, Nf1 þ/À cells displayed increased Ras activity in a pull-down assay, although Ras activity was further increased by BMP-2 treatment (Fig. 1E).…”
Section: Tissue Histologymentioning
confidence: 56%
“…Systemic PTH has been proposed as an alternative anabolic agent for use in NF1, although primarily to target the premature osteoporosis seen in a subset of NF1 patients, rather than for orthopedic applications. 34 PTH is contraindicated in children due to the risk of malignancy in young rats treated with PTH. 35 Next we examined BMP-2-induced bone formation using by direct surgical implantation of rhBMP-2 in a resorbable CMC carrier; a technique that has been previously shown to robustly induce new bone in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Although NF1 haploinsufficient mice have demonstrated reduced responsiveness to parathyroid hormone and abnormal levels of osteoblastic proliferation, apoptosis, and differentiation, the animals had similar bone density to normal mice. 45,46 These studies suggest that although the loss of a single allele increases the risk of osteoblast and osteoblastic progenitor malfunction, there are other pathways that preserve bone homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Although the skeletal involvement of NF1 is well known and osteoporosis has been reported in adults with NF1 (6–8), there is limited data in children. Elucidation of the bone mineral density (BMD) in children with NF1 will provide insight into the aetiology of bone abnormalities, and help in the development of potential therapeutic options (9). Herein, we present and discuss our findings in BMD in children with NF1.…”
Section: Introductionmentioning
confidence: 99%